Efficacy of bimatoprost sustained-release implant in treating severe intraocular pressure in open glaucoma: A meta-analysis - Saad Mutlaq Alosaimi; Ahmad Al Habash; Shahad Salah Alsubhi (Health Sciences Review, 2025)
This meta-analysis investigates the efficacy and safety of the bimatoprost sustained-release (SR) implant for reducing intraocular pressure (IOP) in patients with open-angle glaucoma (OAG), particularly those with severe or uncontrolled IOP. A comprehensive search of multiple databases identified twelve randomized controlled trials including a total of 2808 patients. Pooled analysis demonstrated that the bimatoprost SR implant significantly reduced IOP compared to placebo, with a mean difference of –1.53 mmHg. The implant also increased the proportion of patients achieving desired IOP reduction and was associated with a modest improvement in rescue rates. Adverse events were generally low, with no treatment-emergent adverse events reported in the intervention group. These findings suggest that the bimatoprost SR implant is a safe and effective alternative for patients with OAG who may struggle with adherence to daily eye drops. Further studies are recommended to evaluate its long-term impact on disease progression and visual outcomes.